Global geological occurrence and character of the carcinogenic zeolite mineral, erionite: A review - Patel, Janki Prakash; Brook, Martin S.; Kah, Melanie; Hamilton, Ayrton (Frontiers in Chemistry, 2022)
As with the six regulated asbestos minerals (chrysotile, amosite, crocidolite, anthophyllite, tremolite, and actinolite), the zeolite mineral, erionite, can exhibit a fibrous morphology. When fibrous erionite is aerosolized and inhaled, it has been linked to cases of lung cancers, such as malignant mesothelioma. Importantly, fibrous erionite appears to be more carcinogenic than the six regulated asbestos minerals. The first health issues regarding erionite exposure were reported in Cappadocia (Turkey), and more recently, occupational exposure issues have emerged in the USA. Erionite is now classified as a Group 1 carcinogen. Thus, identifying the geological occurrence of erionite is a prudent step in determining possible exposure pathways, but a global review of the geological occurrence of erionite is currently lacking. Here, we provide a review of the >100 global locations where erionite has been reported, including: (1) geological setting of host rocks; (2) paragenetic sequence of erionite formation, including associated zeolite minerals; (3) fibre morphological properties and erionite mineral series (i.e., Ca, K, Na); and (4) a brief overview of the techniques that have been used to identify and characterize erionite. Accordingly, erionite has been found to commonly occur within two major rock types: felsic and mafic. Within felsic rocks (in particular, tuffaceous layers within lacustrine paleoenvironments), erionite is disseminated through the layer as a cementing matrix. In contrast, within mafic (i.e., basaltic) rocks, erionite is typically found within vesicles. Nevertheless, aside from detailed studies in Italy and the USA, there is a paucity of specific information on erionite geological provenance or fiber morphology. The latter issue is a significant drawback given its impact on erionite toxicity. Future erionite studies should aim to provide more detailed information, including variables such as rock type and lithological properties, quantitative geochemistry, and fiber morphology.